Study of the effect of caffeine on the local formation of the fetus - Fatma Ali Gliwan; Areej Fouad Shakshaka; Sondos Makhlouf Abu Saksaka; Aisha Ramadan Al-Misrati (المجلة الأفروآسيوية للبحث العلمي, 2024)
The stage of embryonic formation in chickens is divided into two parts, and these divisions are helped by the mother’s body temperature through the mother herself incubating the eggs or in the hatchery. The stage of embryonic formation is divided into 3 stages as follows: The first stage lasts from 1-4 days and is called the stage of formation of internal organs. The second stage from 5 - 14 days, which is called the stage of formation of external organs, and the third stage of increase in size, which is from 15-20 days, and is called the growth stage.Caffeine is a commonly used and widespread substance and is one of the most consumed dietary components. It is found naturally in the leaves, seeds and fruits of more than 63 plant species around the world, and is also found in common beverages including coffee, tea and soft drinks.In this research, the effect of caffeine on embryogenesis in local chickens was studied. 90 eggs were collected and divided into three groups. 30 eggs each week were divided into 10 control samples, 10 were injected with a concentration of 1 mM, and 10 were injected with a concentration of 5 mmm. The results showed that excessive concentration of caffeine has harmful effects and deformities, including delayed growth and death of fetuses.It has been shown that the appropriate concentration must be taken into account to obtain the optimal result. When the concentration of caffeine increases significantly, it gives negative results and may lead to deformities. Therefore, studies and experiments must be intensified and knowledge of the use of caffeine concentrations is required because of its effects in any field. life's different aspects